2021
DOI: 10.1186/s12904-021-00746-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial-spiritual interventions among Muslims undergoing treatment for cancer: an integrative review

Abstract: Background Cancer is a global disease that affects all populations, including Muslims. Psychological and spiritual care of Muslim patients with cancer includes psychosocial and spiritual techniques that help to improve their mental health and spiritual well-being. Although these techniques are available to cancer patients worldwide, they are poorly studied among Muslim patients. This review aims to integrate the literature on the psychosocial-spiritual outcomes and perspectives of Muslim patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results showed that religious coping was proven effective in increasing family resilience. This is in line with previous studies which state that positive religious coping protects against negative behaviour (31,32). Although the frequency of religious behaviour is related to anxiety about COVID-19, this anxiety is influenced by the background of religious beliefs and increased stress so individuals increase their prayer and religious meditation to manage their anxiety (33).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that religious coping was proven effective in increasing family resilience. This is in line with previous studies which state that positive religious coping protects against negative behaviour (31,32). Although the frequency of religious behaviour is related to anxiety about COVID-19, this anxiety is influenced by the background of religious beliefs and increased stress so individuals increase their prayer and religious meditation to manage their anxiety (33).…”
Section: Discussionsupporting
confidence: 91%
“…[ 27 ] Training the patient and answering his questions. It is important to provide the patient with the necessary training and answer his questions on these issues: training about discharge and self-care (how to take care of oneself at home[ 34 ] and the discharge process[ 34 ]), answering questions about death and life after death,[ 64 ] answering questions about why I got sick,[ 64 ] talking about nature of the disease and the treatment process[ 8 32 45 46 53 73 ] reporting about the current situation to the patient,[ 39 ] talking about coping with the existing conditions (coping mechanism with the disease[ 49 ] and coping with the sense of loss[ 24 ]), encouraging healthy living (inhaling clean air,[ 59 ] avoiding the health risks,[ 63 ] maintaining the cleanliness and hygiene,[ 43 ] avoiding toxic substances such as cigarettes and alcohol,[ 43 ] and adhering to a vegetarian diet[ 43 ]), increasing the self-awareness (helping the patient to know himself and communicating with himself,[ 48 59 62 74 ] listening to the inner voice,[ 74 ] discussing the patient's values,[ 16 49 ] self-revealing values and spiritual experiences,[ 59 ] expressing concerns,[ 63 ] encouraging to co-ordinate with values,[ 33 ] accepting oneself and reconciling with oneself,[ 33 ] explaining his roles in life,[ 33 ] directing the patient toward self-actualization,[ 33 ] and the recognition of existential capacities),[ 17 49 ] talking about the goals of the patient in life,[ 49 ] increasing individual skills (problem-solving,[ 49 ] positive outlook,[ 62 ] reflect on his experiences,[ 24 ] decision-making,[ 24 ] adjust to the whole situations,[ 24 ] and find the strength to continue[ 24 ]), and providing information according to the patient's need. [ 36 ...…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] Encouraging maintaining and developing social communications. To prevent the isolation of the patient, the following are recommended: Encouraging to communicate with relatives and friends[ 18 33 45 55 59 62 70 73 75 ] (connecting and strengthening the communications and relationships,[ 18 ] sharing thoughts and feelings,[ 31 ] and receiving support from others[ 55 ]), connecting and sharing experiences with other patients,[ 31 ] communicating with care providers,[ 24 ] cooperation and participation in social affairs,[ 31 ] attendance at the workplace,[ 8 ] and participating in spiritual activities. [ 31 ] Contact with other patients with similar illnesses?.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiritually based approaches have been shown to increase breast cancer prevention rates in Afro-American populations [ 36 ]. Although relevant studies from Muslim countries have not led to conclusive results to date [ 37 ], such an approach can be further studied during its application. In the same context, patients diagnosed during the pandemic can be invited to share their experiences given the documented potential of narrative communication in cancer prevention.…”
Section: Recommendations and A Call For Actionmentioning
confidence: 99%